The genetics of cognition in Schizophrenia - Wootton, Olivia (Department of Psychiatry and Mental Health, 2025)
Background: Cognitive impairment is a well-documented feature of schizophrenia and a major determinant of functional outcomes. Cognitive function may be assessed by measuring mean performance measures on cognitive tasks or by measuring variability in performance across tasks or trials of a task that make up a cognitive test battery. Previous research has demonstrated that both cognitive ability and schizophrenia are highly heritable, and that there is a genetic contribution to cognitive impairment in schizophrenia. However, insights into the genetic determinants of cognitive function in schizophrenia remain limited. The overarching aim of the study is to extend current understanding of cognitive impairment in schizophrenia by using previously under-researched or novel metrics of cognitive performance. First, the significance of the phenotype, within-individual variability (WIV) in cognitive performance, was examined in a South African study of people living with schizophrenia. Second, data from the UK Biobank was used to investigate the common genetic determinants of WIV. Third, genetically informed factors corresponding to broad cognitive abilities were used to explore the overlap between the latent cognitive factors, schizophrenia, and schizophrenia symptom dimensions. Methods: A narrative review of the key literature on the clinical, neural, and genetic correlates of WIV was conducted. Multivariable linear regression analyses were then used to assess the relationship between WIV in cognitive performance and selected demographic and clinical variables in 544 people with schizophrenia and 861 matched controls from a South African case-control study. To explore the common genetic basis of WIV, a genome-wide association study (GWAS) of reaction time variability, a measurement of across-task WIV, was conducted in 404,302 individuals from the UK Biobank, a large population-based cohort. Linkage disequilibrium score regression was used to assess the genetic correlations between reaction time variability and selected neuropsychiatric traits, including schizophrenia. Lastly, Genomic Structural Equation Modelling was applied to cognitive data from the UK Biobank to derive latent factors corresponding to broad dimensions of cognitive function. The overlap between the latent cognitive factors, schizophrenia, and schizophrenia symptom dimensions was explored using a variety of statistical approaches, including bivariate MiXeR, the conjunctional false discovery rate method, and polygenic risk score analysis. Results: On a phenotypic level, increased WIV in performance speed across cognitive tests was significantly associated with a diagnosis of schizophrenia, older age, a lower level of education, and a lower score on the global assessment of functioning scale. The GWAS of reaction time variability yielded 161 genome-wide significant single nucleotide polymorphisms distributed across 7 loci, implicating genes involved in synaptic function and neural development. Reaction time variability showed a significant genetic correlation with several traits, including a positive correlation with schizophrenia. Lastly, three latent factors (visuo-spatial, verbal analytic and decision/reaction time) underlying the genetic correlations between the UK Biobank cognitive tests were identified. There was evidence of substantial polygenic overlap between each cognitive factor and schizophrenia but despite the extensive overlap, most significant loci shared between each latent cognitive factor and schizophrenia showed unique patterns of association with the respective factor. Biological annotation of the shared loci implicated gene-sets related to neurodevelopment and neuronal function. Conclusions: The significant relationship between measurements of WIV in performance speed and schizophrenia as well as global functioning in the disorder supports the use of WIV as a measure of cognitive dysfunction in schizophrenia. This thesis demonstrates that reaction time variability is heritable, has a positive genetic correlation with schizophrenia, and that genes associated with reaction time variability have similar biological functions to those affected in schizophrenia. Lastly, substantial overlap in the common genetic influences of latent cognitive factors and schizophrenia was demonstrated. This research suggests that genes related to neurodevelopment and neuronal function underpin cognitive deficits in schizophrenia.